PENDAMPINGAN PERTOLONGAN PERTAMA PADA KECELAKAAN PADA SISWA SMA WISATA DARMA DI DESA LEMBONGAN TAHUN 2018 - Suputra, Putu Adi; Arsani, Ni Luh Kadek Alit; Lestari, Ni Made Sri Dewi (Universitas Pendidikan Ganesha, 2019)
The lack of understanding and skills possessed by the teachers and students of Wisata Darma High School concerning first aid and never had first aid training was a problem found in Lembongan Village. Lembongan village is a tourism village and many emergency cases were found there. The purpose of this activity is to increase the knowledge and skills of students and teachers about first aid in accidents, especially in tourist areas. The method used is lecture, practice, training and mentoring. Participants in this activity are 40 student Wisata Darma High School and 2 accompanying teachers. This activity run well and smoothly. The evaluation was carried out during the implementation of the activity by looking at: attendance of the participants to the end (100%), activeness of the participants during the discussion, and giving tests in the form of pretest, posttest. The results showed an increase in participants' knowledge and participants had skills in conducting first aid. Mentoring is done via email with the accompanying teacher. From this program also produced a pocket book on first aid.